2012
DOI: 10.2147/ndt.s37431
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of milnacipran in treating phantom limb pain

Abstract: BackgroundAmputation of an extremity often results in the sensation of a “phantom limb” where the patient feels that the limb that has been amputated is still present. This is frequently accompanied by “phantom limb pain”. We report here the use of milnacipran, a serotonin and norepinephrine reuptake inhibitor, to treat phantom limb pain after amputation of injured or diseased limbs in three patients.Methods and resultsThe severity of phantom pain before and during treatment was quantified using a visual analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Minimal level 4 evidence exists for the treatment of PLP with mirtazapine, pregabalin, midazolam, milnacipran, fluoxetine, and duloxetine, which includes a small case series and several case reports [146–153].…”
Section: Central Nervous System Mechanisms As a Target For Treatmentmentioning
confidence: 99%
“…Minimal level 4 evidence exists for the treatment of PLP with mirtazapine, pregabalin, midazolam, milnacipran, fluoxetine, and duloxetine, which includes a small case series and several case reports [146–153].…”
Section: Central Nervous System Mechanisms As a Target For Treatmentmentioning
confidence: 99%
“…Although not currently indicated for the treatment of pain, multiple studies indicate that paroxetine, on its own or as a co-therapy, is analgesically efficacious for a variety of human pain conditions. These pain conditions include headache and migraine ( Foster and Bafaloukos, 1994 ; Langemark and Olesen, 1994 ; Holroyd et al, 2003 ; Park et al, 2006 ; Davanzo et al, 2014 ), fibromyalgia ( Patkar et al, 2007 ; Pae et al, 2009a , b ; Ramzy, 2017 ), diabetic neuropathy ( Sindrup et al, 1990 ), irritable bowel syndrome ( Marks et al, 2008 ), burning mouth syndrome ( Maina et al, 2002 ), rheumatoid arthritis ( Bird and Broggini, 2000 ), temporomandibular disorder ( Inagaki et al, 2007 ), noncardiac chest pain ( Doraiswamy et al, 2006 ), phantom limb pain ( Nagoshi et al, 2012 ), and somatic pain comorbid with the disorders for which paroxetine is indicated ( Aikens et al, 2008 ; Wise et al, 2008 ; Hollander et al, 2010 ). However, one lumbar chronic back pain study found a nonsignificant 25% reduction in pain intensity ( Atkinson et al, 1999 ), and case studies reveal that paroxetine may not be appropriate for rare pain conditions ( Zhu et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serotonin-norepinephrine reuptake inhibitors (SNRIs) are popular for neuropathic pain, migraines, and fibromyalgia due to fewer side effects contrary to tricyclic antidepressants (TCAs) and equal efficacy 4 . Milnacipran and duloxetine has already been approved by FDA for fibromyalgia due to its action on noradrenergic and serotonergic fibers in descending inhibitory pain pathways as noted by Barkin and Fawcett 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides these theories no one separately explain the PLP and it believed that multiple mechanisms are potentially responsible 2 . The serotoninnorepinephrine reuptake inhibitors (SNRIs) which may target central mechanisms 3 , are popular for neuropathic pain, migraines, and fibromyalgia due to efficacy and fewer side effects 4 .…”
Section: Introductionmentioning
confidence: 99%